Gendered Bullying and Cyberbullying: Assessing Ontario’s New Legislation - Rebecca, Katz (Université d'Ottawa / University of Ottawa, 2014)
This research considers gendered bullying and cyberbullying and assesses the ways Ontario's reformed Education Act confronts these challenges. This thesis reviews the problems of homophobic and sexist bullying, particularly sexist bullying of young women in the wake of sexting incidents, as well as protective factors to minimize gendered bullying in school and online. The new Education Act represents a significant step forward in encouraging schools to better respect the rights of sexual and gender minority students and female students. However, the Act nevertheless has several weaknesses in key areas such as concrete implementation measures.
Keywords: bullying; cyberbullying